Ausencia de un sistema jurídico que permita el control del efectivo uso y goce de las pensiones alimenticias en materia de niñez y adolescencia ecuatoriana - Pérez Zambrano, Susy Denise (2016)
The present investigation has by subject “ABSENCE OF A JURIDICAL SYSTEM THAT ALLOW THE CONTROL OF THE EFFECTIVE USE OF THE ALIMENTARY PENSIONS IN MATTER OF CHILDHOOD And ECUADORIAN ADOLESCENCE” In a society in which the right does to prevail in the legal norm the equality established in the Constitution of the Republic, cannot allow under any circumstance the abuse neither the excesses of a person to another, is not in vain the Latin aphorism “the right of a person finishes where begins the one of the another. I have here the problem when we speak of the right of the boys to perceive foods, so that it remain clear in this occasion will not argue with regard to if the minor has or not the right to receive nutrition or on the upper interest of the that this enjoys and took him the law, but of the moral and juridical obligation of the person called to respect and enforce these rights…..